2004
DOI: 10.1166/jnn.2004.003
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of Gold Nanocrystals and Its Role in Determining the Stability of Surface Thiol Monolayers

Abstract: Colloidal gold nanocrystals were found to be efficient photocatalysts for the oxidation of thiols to the corresponding disulfide in aqueous solution under UV radiation, although no noticeable catalytic effect of gold nanocrystals was observed under dark conditions for the same process. The turnover number per particle increased with the size of the nanocrystals and reached 1200 molecules/s for 45-nm gold nanocrystals. The photochemical instability of colloidal gold nanocrystals coated by thiol ligands was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Short linkers may provide an increased assay sensitivity [24] but may also lead to poor solubility. [22] Additionally, Li and Peng have shown that the photochemical stability of AuNPs is dependent on the length of the linker; [43] long alkanethiolate linkers provide improved stability over shorter linkers. In light of these considerations, we chose to work with OEG linkers consisting of thiol-terminated tetra(ethylene glycol).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Short linkers may provide an increased assay sensitivity [24] but may also lead to poor solubility. [22] Additionally, Li and Peng have shown that the photochemical stability of AuNPs is dependent on the length of the linker; [43] long alkanethiolate linkers provide improved stability over shorter linkers. In light of these considerations, we chose to work with OEG linkers consisting of thiol-terminated tetra(ethylene glycol).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…The synthesis and properties of metallic nanoparticles (NPs) has been extensively studied over decades, not only because of their unique properties, but also because of their potential applications in catalysis, electronics, optoelectronics, information storage, biosensors, and surface-enhanced Raman spectroscopy (SERS) [1][2][3][4][5][6][7][8][9][10]. Nanoparticles can exist as common structural elements or composites, and they have a wide functional diversity compared to bulk materials.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary interactions attributed to aurophilicity have been calculated to be 21-46 kJ/mol, which is on the order of the dissociation energy of a hydrogen bond. Larger clusters of Cu n , Ag n , and Au n (n ) 5-8) have been investigated through a variety of techniques and have been used as catalysts, [31][32][33][34][35][36][37] semiconductors, optical devices, pharmaceuticals, and antimicrobial agents. [38][39][40][41] Two-coordinate gold complexes are usually colorless; however, they can be luminescent depending on the ligand and the extent of metal-metal interaction.…”
Section: Introductionmentioning
confidence: 99%